A dynamic microscale mid-throughput fibrosis model to investigate the effects of different ratios of cardiomyocytes and fibroblasts. Issue 21 (21st September 2021) - Mainardi, Andrea; Carminati, Francesca; Ugolini, Giovanni Stefano; Occhetta, Paola; Isu, Giuseppe; Robles Diaz, Diana; Reid, Gregory; Visone, Roberta; Rasponi, Marco; Marsano, Anna
Abstract : High percentages of cardiomyocytes mitigate the onset of fibrotic traits induced by fibroblasts in a mid-throughput, mechanically active microdevice. Abstract : Cardiac fibrosis is a maladaptive remodeling of the myocardium hallmarked by contraction impairment and excessive extracellular matrix deposition (ECM). The disease progression, nevertheless, remains poorly understood and present treatments are not capable of controlling the scarring process. This is partly due to the absence of physiologically relevant, easily operable, and low-cost in vitro models, which are of the utmost importance to uncover pathological mechanisms and highlight possible targets for anti-fibrotic therapies. In classic models, fibrotic features are usually obtained using substrates with scar mimicking stiffness and/or supplementation of morphogens such as transforming growth factor β1 (TGF-β1). Qualities such as the interplay between activated fibroblasts (FBs) and cardiomyocytes (CMs), or the mechanically active, three-dimensional (3D) environment, are, however, neglected or obtained at the expense of the number of experimental replicates achievable. To overcome these shortcomings, we engineered a micro-physiological system (MPS) where multiple 3D cardiac micro-tissues can be subjected to cyclical stretching simultaneously. Up to six different biologically independent samples are incorporated in a single device, increasing the experimental throughput and paving the way for higher yielding drug screening campaigns. The newly developed MPS was used to co-culture different ratios of neonatal rat CMs and FBs, investigating the role of CMs in the modulation of fibrosis traits, without the addition of morphogens, and in soft substrates. The expression of contractile stress fibers and of degradative enzymes, as well as the deposition of fibronectin and type I collagen were superior in microtissues with a low amount of CMs. Moreover, high CM-based microconstructs simulating a ratio similar to that of healthy tissues, even if subjected to both cyclic stretch and TGF-β1, did not show any of the investigated fibrotic signs, indicating a CM fibrosis modulating effect. Overall, this in vitro fibrosis model could help to uncover new pathological aspects studying, with mid-throughput and in a mechanically active, physiologically relevant environment, the crosstalk between the most abundant cell types involved in fibrosis.